2006
DOI: 10.1074/jbc.m509503200
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of β1-Adrenergic Receptor Interactions with PDZ Scaffold Proteins

Abstract: Many G protein-coupled receptors possess carboxyl-terminal motifs ideal for interaction with PDZ scaffold proteins, which can control receptor trafficking and signaling in a cell-specific manner. To gain a panoramic view of ␤ 1 -adrenergic receptor (␤ 1 AR) interactions with PDZ scaffolds, the ␤ 1 AR carboxyl terminus was screened against a newly developed proteomic array of PDZ domains. These screens confirmed ␤ 1 AR associations with several previously identified PDZ partners, such as PSD-95, MAGI-2, GIPC, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
135
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 110 publications
(135 citation statements)
references
References 30 publications
0
135
0
Order By: Relevance
“…GST and GST-CRFR1 fusion proteins bound to the matrix were washed extensively in PBS-containing 0.3% Triton X-100. 100 nM GST and GST-CRFR1 in blot buffer (2% nonfat dry milk, 0.1% Tween 20, 50 mM NaCl, 10 mM HEPES, pH 7.4) were incubated with gridded nylon membranes that were spotted with His/S-tagged PDZ domain fusion proteins (1 g/bin) for 1 h at room temperature (23,24). The arrays were then washed three times with blot buffer and incubated with a horseradish peroxidase-conjugated anti-GST antibody (1:3000).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GST and GST-CRFR1 fusion proteins bound to the matrix were washed extensively in PBS-containing 0.3% Triton X-100. 100 nM GST and GST-CRFR1 in blot buffer (2% nonfat dry milk, 0.1% Tween 20, 50 mM NaCl, 10 mM HEPES, pH 7.4) were incubated with gridded nylon membranes that were spotted with His/S-tagged PDZ domain fusion proteins (1 g/bin) for 1 h at room temperature (23,24). The arrays were then washed three times with blot buffer and incubated with a horseradish peroxidase-conjugated anti-GST antibody (1:3000).…”
Section: Methodsmentioning
confidence: 99%
“…We have investigated the capacity of the CRFR1 carboxylterminal tail to bind to a proteomic array of 96 class I PDZ domains (23,24). We found that the CRFR1 carboxyl-terminal tail binds to a selective subset of class I PDZ domains on the array.…”
Section: Corticotropin-releasing Factor (Crf)mentioning
confidence: 99%
“…The PDZ-array overlay assay was performed as described [10,12]. Briefly, a nylon membrane spotted with a series of His/Stagged PDZ domain proteins was pre-treated with a blocking buffer containing 2% non-fat dry milk and 0.1% Tween-20 in 150 mM NaCl and 10 mM phosphate buffer, pH 7.3 (PBS) for 30 min, then overlaid with the GST-fused proteins (15 nM) in the blocking buffer.…”
Section: Overlay Assay On the Pdz Arraymentioning
confidence: 99%
“…We screened for potential interactions between Na x and PDZ proteins using the PDZ-array overlay assay [10,12] with the GSTfused protein with the C-terminal region of Na x (GST-Na x -C-term) (Fig. 1).…”
Section: Identification Of Pdz Proteins That Interact With Na Xmentioning
confidence: 99%
See 1 more Smart Citation